Fostering Student Satisfaction in Higher Education: Is it Possible to Enhance the Quality of Learning through Wordwall? - Enny Kartini; Syarifah (Journal of Education Technology, 2025)
The integration of digital technology in higher education presents both opportunities and challenges in ensuring learning quality that meets students’ expectations. One of the main issues is the gap between students’ perceptions of the performance of digital learning media and their perceived importance, which affects learning satisfaction. This study aims to evaluate the quality of Wordwall-based learning in enhancing students’ satisfaction using the Importance-Performance Analysis (IPA) approach. The study employed a descriptive quantitative method involving 81 students from the Economics Education Study Program who were enrolled in a microeconomics course. Data were collected through an online questionnaire consisting of 10 performance items and 10 importance items based on the five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. Data analysis was conducted using IPA and a paired sample t-test. The results indicate a significant difference between students perceived performance and expectations regarding the use of Wordwall (p < 0.05). Attributes located in Quadrant I, including Wordwall interface, content consistency, and learning flexibility, were considered highly important but did not meet students’ expectations and therefore require improvement. Meanwhile, accessibility, ease of use, and immediate feedback were located in Quadrant II and should be maintained, as they have met students’ expectations. This study concludes that Wordwall has considerable potential to support interactive learning in higher education; however, its effectiveness largely depends on implementation strategies, feature selection, and institutional support to enhance students’ learning satisfaction.